EFFECT OF WOOD ASH, POULTRY MANURE AND NPK FERTILIZER ON SOIL AND LEAFNUTRIENT COMPOSITION, GROWTH AND YIELD OF OKRA (ABELMOSCHUS ESCULENTUS) - Agbede, T. M.; Adekiya, A. O. (Emirates Journal of Food and Agriculture, 2017)
The data on poultry manure (PM), wood ash (WA) and NPK fertilizer are needed to identify strategies for sustainable management of a degraded Alfisol for improving agronomic productivity. Hence field experiments were conducted at Owo in the forest-savanna transition zone of southwest Nigeria to study the effects of organic amendments and NPK fertilizer on the soil chemical properties, leaf nutrient concentrations, growth and pod yield of okra. Seven treatments considered in 2006, 2007 and 2008 were control (no manure/fertilizer), 5.0 t ha- 1 PM, 10.0 t ha-1 PM, 5.0 t hav WA, 10.0 t ha-1 WA, 5.0 t ha-1 PM + 5. 0 t ha-1 WA and NPK 15-15-15 (200 kg ha-1 ) fertilizer. The treatments were laid out in a randomized complete block design with three replications. Organic amendments (PM and WA) improved soil organic C, N, P, K, Ca and Mg and leaf N, P, K, Ca and Mg concentrations, growth and yield of okra compared with the control. NPK 15-15-15 fertilizer increased soil N, P and K, but did not increase soil organic C, Ca and Mg and leaf Ca and Mg of okra. Combined application of 5.0 t ha-1 PM + 5.0 t ha-1 WA mostly improved leaf and soil N, P, K, Ca and Mg and soil organic C, growth and okra yield compared with other treatments. The superior performance of 5.0 t ha-1 PM + 5.0 t ha-1 WA was adduced to increased availability of nutrients following the inclusion of PM which aided faster decomposition and release of nutrients. Relative to the control, using the mean of the 3 years, 5.0 t ha-1 WA, 5.0 t ha-1 PM, NPK fertilizer, 5.0 t ha-1 PM + 5.0 t ha-1 WA, 10.0 t ha-1 WA and 10.0 t ha-1 PM increases pod yield by 23, 64, 68, 255, 41 and 123%, respectively. Combined use of PM and WA is recommended for ameliorating degraded Alfisol of southwest Nigeria and also reduced the quantities of PM and WA required for soil fertility maintenance.